الالتزام الدينيّ في رواية قضية أبو الفتوح الشرقاوي لنجيب الكيلاني - Abdul Badihi Uthman
This research work examines the extent of religious commitment in one of Dr. Najib Kaylani’s novels titled: Riwayatu Qadiyati Abul Futuh Ash-Sharqawiy. The novel, among other things, is an admixture of tragedy and comedy characterized and influenced by Islamic thoughts. This is because there is a group of youths in the novel concerned with the diffusion of Islamic teachings and moral values in the society, in accordance with what is contained in the noble Islamic law; while the affair of another group is dedicated to holding gatherings for the remembrance of Allah. The researcher employed two methods, for the purpose of achieving the objectives behind the study; they are: inductive and descriptive analytical methods. These were used for the identification of the novel’s characters, different roles played by the individuals among the characters, and explanation of some hidden facts contained in the novel. At the end of the day, the research came out with the fact that the novel under study mirrors a typical Islamic society; as this is perceived by the researcher in all facets of the novel’s components. More especially, the exploration of the series of episodes reveals that the language and styles used are characterized by a number of quotations drawn from the Quranic verses. Thus, this only gives credence to and implies that the novel is of utmost connection with the religious commitment.